PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPA DENGAN MENGGUNAKAN PENDEKATAN KONSTRUKTIVISME DI SEKOLAH DASAR - PUTRI, VENNY EKA (Universitas Negeri Padang, 2014)
Abstract The aim of this research was to increase the students’ learning achievement in Natural Science by using Constructivism approach in grade V of SDN 19 Koto Tuo Selatan. This classroom Action Research applied both qualitative and quantitative approaches. The subject of the research was the teacher and 20 students in grade V of SDN 19 Koto Tuo Selatan. This research was conducted in two cycles in which each cycle consisted of planning, acting, observing and reflecting. The instruments of the research were test and observation sheet. The result of the research showed that the students’ learning achievement improved from 72 in cycle I to 87 in cycle II. Key Terms : Approach, Natural Science Learning dan Constructivism Approach